PEMBERIAN BERBAGAI DOSIS PUPUK KANDANG AYAM TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN BAWANG DAUN (Allium fistulosum L.). - Maisa, Maisa; Yetti, Husna (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
This study aims to determine the effect of chicken manure and the best dosage for the growth and production of leek (Allium fistulosum L.). Research has been conducted at the Experimental station, Faculty of Agriculture, University of Riau, Pekanbaru. The research was conducted as experiments using a randomized block design (RAK) consisting of six levels and four replications, from July to September 2017. Parameters measured were plant height, number of tillers, weight per hill, fresh weight, the weight for consumption and volume the root. Results the reserch show that several doses of chicken manure significantly increased the plant height, number of tillers, weight per hill, fresh weight, but not for proper weight is for consumption and the root volume. Provision of chicken manure with a doses of 17.5 ton.ha-1 showed a better improvement on the growth and yield of leek.Keywords : leek, doses, chicken manure